2022
DOI: 10.3389/fmars.2022.826421
|View full text |Cite
|
Sign up to set email alerts
|

Global Synthesis of Air-Sea CO2 Transfer Velocity Estimates From Ship-Based Eddy Covariance Measurements

Abstract: The air-sea gas transfer velocity (K660) is typically assessed as a function of the 10-m neutral wind speed (U10n), but there remains substantial uncertainty in this relationship. Here K660 of CO2 derived with the eddy covariance (EC) technique from eight datasets (11 research cruises) are reevaluated with consistent consideration of solubility and Schmidt number and inclusion of the ocean cool skin effect. K660 shows an approximately linear dependence with the friction velocity (u*) in moderate winds, with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 67 publications
2
35
0
Order By: Relevance
“…The data clearly imply values of CE on the order 4-6 cm hr -1 at the lowest wind speeds but even at U 10 = 5 ms -1 it is doubtful the difference between observations of Dk and the estimates of the bubble component are significant. This result is similar to (Yang et al, 2022) who computed a grand-averaged k c660 from eight field programs (including the ones used here) and estimate CE by differencing their average with dual tracer estimates of k c660 (Ho et al, 2006). Because the dual tracer studies are done with non-reactive gases, the argument is that they do not include CO 2 CE.…”
Section: Chemical Enhancementsupporting
confidence: 77%
See 1 more Smart Citation
“…The data clearly imply values of CE on the order 4-6 cm hr -1 at the lowest wind speeds but even at U 10 = 5 ms -1 it is doubtful the difference between observations of Dk and the estimates of the bubble component are significant. This result is similar to (Yang et al, 2022) who computed a grand-averaged k c660 from eight field programs (including the ones used here) and estimate CE by differencing their average with dual tracer estimates of k c660 (Ho et al, 2006). Because the dual tracer studies are done with non-reactive gases, the argument is that they do not include CO 2 CE.…”
Section: Chemical Enhancementsupporting
confidence: 77%
“…Because the dual tracer studies are done with non-reactive gases, the argument is that they do not include CO 2 CE. Yang et al (2022) found CE values of about 4 cm hr -1 for U 10 < 10m s -1 . These results suggest t r on the order of 3 s (a r = 0.33) should be used in (38) to estimate CE if the difference between CO 2 and dual tracer is due to chemical enhancement only.…”
Section: Chemical Enhancementmentioning
confidence: 89%
“…This O/E air–sea flux observations and analysis have also provided: the first Southern Ocean evidence for the suppression of CO 2 gas exchange velocity due to the presence of surface surfactants [ 24 ], an important finding particularly for Earth system models; information on the role of ice melt in air–sea CO 2 flux estimates [ 11 , 25 , 26 ]; the first global synthesis of air–sea CO 2 gas exchange velocity measurements derived from eddy covariance, demonstrating that earlier and widely used geochemical tracer-based CO 2 exchange estimates were likely underestimated at low wind speeds [ 27 ]; and the discovery that SST variability in the Southern Ocean demonstrates scale-invariant (fractal) properties, making it plausible that SST can be statistically extrapolated from coarser to finer spatial scales [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…δFCO2=(0.2)2+(0.003)2+(0.057)2+(0.0006)20.2 $\delta {F}_{{CO}_{2}}=\sqrt{{(0.2)}^{2}+{(0.003)}^{2}+{{(0.057)}^{2}+(0.0006)}^{2}}\approx 0.2$ In the process of calculating CO 2 air‐sea flux, many algorithms have been put forth which relate the gas transfer velocities to a variety of factors regulating the transfer of gases across the air‐sea boundary (Garbe et al., 2014; Gutierrez‐Loza et al., 2022; Leighton et al., 2018; Ribas‐Ribas et al., 2018; Yang et al., 2021). Empirical formulations which relate transfer velocities to wind speeds have reported quadratic (Wanninkhof 2014; Prytherch & Yelland 2021) or higher dependencies and even other functionalities (Deiki & Melville 2018; Frankignoulle, 1988; Gu et al., 2021b; Li et al., 2021; Monahan & Spillane 1984; Wanninkhof & McGillis, 1999; Wanninkhof et al., 2009; Yang et al., 2022). Wanninkhof (1992) showed that a quadratic dependence exists between gas transfer velocities and wind speeds within the range of global wind speeds of 0–30 m/s determined at intervals of 0.5 m/s.…”
Section: Methodsmentioning
confidence: 99%